Cognitive skills and reading in adults with Usher syndrome type 2 - Henricson, Cecilia; Lidestam, Björn; Lyxell, Björn; Möller, Claes (Frontiers in Psychology, 2015)
Objective: To investigate working memory, phonological skills, lexical skills, and reading comprehension in adults with Usher syndrome type 2 (USH2). Design: The participants performed tests of phonological processing, lexical access, working memory and reading comprehension. The design of the test situation and tests was specifically considered for use with persons with low vision in combination with hearing impairment. The performance of the group with USH2 on the different cognitive measures was compared to that of a matched control group with normal hearing and vision (NVH). Study Sample: Thirteen participants with USH2 aged 21–60 years and a control group of ten individuals with NVH, matched on age and level of education. Results: The group with USH2 displayed significantly lower performance on tests of phonological processing, and on measures requiring both fast visual judgment and phonological processing. There was a larger variation in performance among the individuals with USH2 than in the matched control group. Conclusions: The performance of the group with USH2 indicated similar problems with phonological processing skills and phonological working memory as in individuals with long-term hearing loss. The group with USH2 also had significantly longer reaction times, indicating that processing of visual stimuli is difficult due to the visual impairment. These findings point toward the difficulties in accessing information that persons with USH2 experience, and could be part of the explanation of why individuals with USH2 report high levels of fatigue and feelings of stress (Wahlqvist et al., 2013).